Electromagnetic and thermal stability of the ITER Central Solenoid during a 15 MA plasma scenario. (19th June 2019) - Bagni, T; Devred, A; Nijhuis, A
Abstract: The combination of the electromagnetic conductor model JackPot ACDC with the thermo-hydraulic model THEA is able to reproduce and predict the behavior of cable-in-conduit conductors (CICCs) under any varying current and magnetic field. The combined JackPot-THEA model is used to simulate the turns of the CSU2 quadra-pacake of the ITER Central Solenoid (CS) that are subjected to the most demanding conditions of the 15 MA plasma scenario. The considered section is a pancake with a 150 m length of Nb3 Sn CICC from helium inlet to helium outlet, from the inner towards outer turns. The simulation results in terms of temperature and local strand electric field levels are compared to those obtained from earlier minimum quench energy analysis in order to evaluate possible risk of quench. The results confirm sufficient stability of the ITER CS coil, both from electrical and thermal point of view. The temperature evolution and flow of a helium heat slug along the conductor during the 15 MA plasma scenario is also analyzed. It appeared that sequential multiple burn cycles can be carried out without accumulation of temperature in the helium heat slug, essential for continuous energy production for a fusion power plant.